Using the Flipped Classroom Model to Prevent Sexual Violence in Special Needs Children - Mutiawati, Mutiawati; Syahputra, Andy; Nelly, Nelly; Yusian, Desita Ria; Lestari, Soraya; Rusyidah, Rusyidah; Saudah, Saudah (Journal of Educational Management and Learning, 2023)
The Flipped Classroom learning is designed to develop a future learning model for Special Needs Children (SNC). This article investigates students' perceptions of the impact of learning transitions on the prevention and handling of sexual violence in integrated children with disabilities using gender mainstreaming principles and teacher beliefs. This research utilizes a mixed methods approach within a concurrent design structure that combines primary research using quantitative surveys with semi-structured qualitative interviews. The delivery of sex abuse material through traditional methods such as lectures or tutorials is replaced with flipped Classroom learning through instructional videos. This study found that the transition was generally well-received by students with SNC in inclusive schools. Engaged students tended to perform well in the flipped Classroom learning environment. However, scaffolding in the form of teacher beliefs and gender mainstreaming to prepare students for the transition to flipped Classroom learning is key to promoting knowledge acquisition, performance, engagement, collaboration, and overall positive student experiences.